A Prospective Randomised Trial of Nifedipine Versus Placebo in Preterm Labour (Bangladesh Journal of Obstetrics & Gynaecology, 2010)
Objective: To evaluate nifedipine as a tocolytic agent and measure the side-effectsMethods : Prospective randomized study of 89 singleton pregnancies with preterm labour between 30-34 weeks of gestation. The capacity to delay delivery 48 h,7 days, til 36 weeks were the outcome variable assessed.Results: Nifedipine could successfully prolong delivery in about 82 % of cases. There were fewer side-effects. Main side-effects were flushing and head-ache. Most of the patients complained of no side-effects.Conclusion : Nifedipine is a well tolerated tocolytic drug with fewer side-effects.Key word: Nifedipine; tocolysis; preterm labourBangladesh J Obstet Gynaecol, 2008; Vol. 23(2) : 61-64